Faktor-Faktor Yang Berhubungan dengan Kejadian Stunting Pada Balita di Wilayah Kerja Puskesmas Bakunase Kota Kupang - Hendrika Octavia Nugraheni Kitu; Yendris Krisno Syamruth; Sigit Purnawan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Stunting or short stature is a term used for children whose height is below average (<-2 SD) of the same sex, chronological age and ideally from the same racial-ethnic group. Stunting can cause children to experience health problems during their growth and development, even irreversible. In the short term, stunting causes a slowdown in the process of growth and development and in the long term it will have an impact on cognitive aspects and the possibility of non-communicable diseases. Therefore, the incidence of stunting is an indicator of child welfare in a country. This study aims to analyze the factors associated with the incidence of stunting in toddlers in the Bakunase Community Health Center, Kupang City. This type of research is an analytical survey, with a case control design. The number of samples was 136 people which were divided into 68 case groups and 68 control groups. The data analysis technique used the chi-square statistical test. The results showed that there was a relationship between mother's knowledge (p value = 0.000, OR = 6.667), mother's attitude (p value = 0.000, OR = 5.808), mother's parenting style (p value = 0.000, OR = 5.093), living environment ( p value = 0.000, OR = 7.538), and the incidence of diarrhea (p value = 0.002, OR = .3.175) with the incidence of stunting in toddlers in the Working Area of the Bakunase Health Center, Kupang City. Therefore, health promotion and cross-sector cooperation are needed to overcome the problem of stunting.